Reproductive Health Literacy Among Adolescents in Pekanbaru: A Cross- Sectional Study - Masrina Munawarah Tampubolon; Nurhannifah Rizky Tampubolon; Niken Yuniar Sari; Arneliwati Arneliwati (Universitas Pahlawan Tuanku Tambusai, 2026)
Reproductive health literacy is a foundational element in promoting sustainable public health, particularly among adolescents. Despite its importance, global and national studies consistently report low literacy levels in this domain. This cross-sectional study aimed to assess the reproductive health literacy of junior high school students in Pekanbaru, Indonesia, with a specific focus on gender-based disparities. A total of 323 students were purposively selected and surveyed using a highly reliable instrument adapted from the Health Literacy Measure for Adolescents (HELMA), which evaluates five key domains: accessing, reading, understanding, appraising, and applying health information. Findings revealed that 91.02% of respondents fell into the “inadequate” literacy category, with no participants achieving an “excellent” level. Gender analysis showed that 95.04% of male and 87.91% of female students were classified as having inadequate literacy, while only 3.72% reached a “sufficient” level. Although female students exhibited slightly higher proportions in the “problematic” and “sufficient” categories, the overall literacy remained critically low across both genders. Domain-specific analysis indicated stronger conceptual understanding among adolescents but significant weaknesses in functional and critical literacy skills. This study contributes novel insights by documenting lower literacy levels than previously reported in national and international contexts, and by offering a detailed breakdown across literacy domains. The results underscore the urgency of implementing targeted, domain-based, and gender-sensitive educational interventions. Furthermore, the findings advocate for a locally grounded, collaborative approach involving schools, healthcare providers, families, and digital media to cultivate a supportive information ecosystem that empowers adolescents in making informed reproductive health decisions.